Peran Kegiatan Intrakurikuler dan Ekstrakurikuler dalam Penguatan Karakter dan Kompetensi Sosial Siswa di Lingkungan Sekolah - Syaharuddin Syaharuddin; M. Yamin; Ayu Hesti; Fitri Fitri; Fina Elisa Putri; Indah Rahmawati; Imam Saputra; Fira Yuniar; Muhammad Fatteh (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2026)
Intracurricular and extracurricular activities play a strategic role in shaping students’ character and social competence amid the challenges of modern education, which demand not only academic achievement but also the strengthening of moral values, ethics, and social skills. The urgency of this study is based on the need for schools to systematically integrate character education through activities inside and outside the classroom. This study aims to describe the role of intracurricular and extracurricular activities in strengthening character and developing students’ social competence at SMP IT Anak Sholeh Mataram. The method used is a qualitative approach with a descriptive research design. The research subjects include the principal, the vice principal for curriculum, and the vice principal for student affairs. The research instruments consist of observation sheets and interview guidelines containing 12 questions in six categories: character education, intracurricular activities, extracurricular activities, activity impacts, evaluation, and challenges and support. The research procedure was conducted through data collection, data reduction, data display, and conclusion drawing based on the Miles and Huberman model. The results indicate that intracurricular activities integrated with spiritual habituation, contextual learning, and active learning methods are able to instill values of discipline, responsibility, and cooperation. Meanwhile, extracurricular activities such as Scouts, OSIS (Student Council), and Basic Leadership Training contribute significantly to fostering leadership, empathy, social solidarity, and students’ interpersonal skills. The conclusion of this study confirms that the systematic integration of intracurricular and extracurricular activities, supported by teacher involvement and continuous evaluation, is effective in strengthening students’ character and social competence. The implications of this study highlight the need to strengthen collaboration among teachers, develop sustainable character-building programs, and enhance educators’ capacity through training so that character education can be implemented more optimally.